L’image du « turc » dans la prose bulgare des XIXe et XXe siècles - Marie Vrinat-Nikolov (Cahiers Balkaniques, 2008)
This article analyzes the portrayal of the Ottoman (generally called the “Turk”) given to us by Bulgarian writers. Beginning with the negative image inherited from the past, since The Slavo-Bulgarian History written in 1762 by Païsii de Khilendar and the Life and Tribulations of Sophroni the Sinner by Sophroni of Vratsa (1805-1812?), the continuity of this portrayal is followed along with that of the topoï that it encouraged in the post-liberation Bulgarian prose until the middle of the twentieth century, along with its variations. The article attempts to understand what motivated, in the different political and social contexts, the appearance of these negative images and finds that it seems very much tied to the metamorphoses in domestic politics, the way in which Bulgaria lived through the post-Ottoman period, the policies of the Bulgarian government in regard to its Muslim citizens of Turkish origins (the Pomaks), and finally Bulgaria’s relations with the USSR and Turkey. Finally, a Romanesque typology will be established dealing with the manner in which the Ottoman is treated in this prose.